Development of Guided Inquiry-Based Microbiology Modules Based on the Identification of Contaminant Molds in Tomato Fruit to Improve Students' Science Process Skills - Naufal Wima Al Fahri; Utami Sri Hastuti; Safwatun Nida (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
Students often experience difficulties in identifying microbiological specimens due to limitations in preparing and interpreting microscopic slides. This problem is evident in the context of tomato fruits (Solanum lycopersicum), which are widely consumed agricultural commodities but are highly perishable and susceptible to microbial contamination, especially by molds. To address this challenge, this study aims to develop a guided inquiry-based microbiology learning module using tomato mold identification as a case study, with the goal of improving students’ Science Process Skills (SPS). The research was conducted in two stages: (1) laboratory experiments to identify contaminant molds in tomatoes and (2) development of a learning module using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The sample consisted of 62 microbiology students from the Biology Education Program, Faculty of Mathematics and Natural Sciences, State University of Malang. A non-randomized control-group pretest–posttest design was employed, the increase in posttest results compared to the pretest was calculated using the N-gain score. Results showed that students’ SPS was still relatively low, particularly in the observing indicators (30.43%) and hypothesizing indicators (43.48%). The developed module integrates real laboratory findings into structured inquiry-based activities, emphasizing hands-on practice, critical thinking, and contextual relevance to agricultural microbiology. Its distinctive features include the use of authentic microbial identification data, scaffolding through guided inquiry steps, and alignment with SPS indicators. This module is expected to provide an effective solution for enhancing students’ SPS in microbiology learning